Microbiology of blenderized whole food tube feedings from selected hospitals of the National Capital Region, Philippines - Quiambao, Michelle Leslie C.; Gabriel, Alonzo (2006)
ABSTRACT Blenderized whole food tbe feedings (BTF) (n=30) from selected Philippine tertiary and specialty hospitals (n=10) in the National Capital Region (NCR) were analyzed for microbial contamination. Standard limits established by the US Food and Drug Administration (FDA) (1998) for medical foods were used as threshold values. Total Plate Counts (TPC) ranged from <3.40 to 7.19 log 10 CFU/ml while the Staphylococcs aureus population ranged from <3.30 to 5.41 log10 CFU/mL. Total coliforms (TC) were found to vary between <4.18 to 4.33 log10 CFU/mL and generic Escherichia coli was reported to be <4.18 log10 CFU/mL. Twenty-five of the analyzed samples were positive for Salmonella spp. Unhygienic handling practices, poor personal hygiene, and improper holding conditions were identified as possible factors that affect microbial growth in BTFs. Thus, the implementation of Good Hygienic and Manufacturing Practices (GHP/GMP)and the Hazard Analysis and Critical Control Point (HACCP) systems are highly recommended in order to comply with established international food microbiological quality standards.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Food -- Microbiology; Hospitals -- Food service. -- Philippines -- National Capital Region; Food -- Safety measures